2022
DOI: 10.7554/elife.76107
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of dynamic P5CS filaments

Abstract: The bifunctional enzyme Δ1-pyrroline-5-carboxylate synthase (P5CS) is vital to the synthesis of proline and ornithine, playing an essential role in human health and agriculture. Pathogenic mutations in P5CS gene (ALDH18A1) lead to neurocutaneous syndrome and skin relaxation connective tissue disease in humans, and P5CS deficiency seriously damages the ability to resist adversity in plants. We have recently found that P5CS forms the cytoophidium in vivo and filaments in vitro. However, it is difficult to apprec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Compared with dmP5CS, the regulation of atP5CS2 filament is different. For dmP5CS, the contribution of glutamate is greater than ATP 7 . For atP5CS2, both glutamate and ATP promote filament formation at similar degrees ( Figure 2 C ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Compared with dmP5CS, the regulation of atP5CS2 filament is different. For dmP5CS, the contribution of glutamate is greater than ATP 7 . For atP5CS2, both glutamate and ATP promote filament formation at similar degrees ( Figure 2 C ).…”
Section: Resultsmentioning
confidence: 90%
“…Some well-studied filamentous enzymes, like CTPS and PRPS, have shown that their filamentation is conserved across a wide range of species [36][37][38][39][40][41] . In previous studies, we found dmP5CS could form cytoophidia and filament, and the filament is critical for its activity 7 . But the conservation of P5CS filament was not clear.…”
Section: Conservation Of the P5cs Filamentmentioning
confidence: 88%
See 2 more Smart Citations
“…More than 20 different metabolic enzymes form filaments in cells, suggesting that filament assembly is a general mechanism for regulating multiple metabolic pathways (Hvorecny and Kollman, 2023; Lynch et al, 2020; Narayanaswamy et al, 2009; Noree et al, 2010; Park and Horton, 2019; Park and Horton, 2020; Shen et al, 2016; Simonet et al, 2020). For many metabolic enzymes, filament formation is an important mechanism for fine-tuning catalytic activity (Barry et al, 2014; Hansen et al, 2021; Hu et al, 2022; Hunkeler et al, 2018; Hvorecny et al, 2023; Lu et al, 2023; Lynch and Kollman, 2020; Lynch et al, 2017; Polley et al, 2019; Stoddard et al, 2020; Zhong et al, 2022). Here, we demonstrate that filament assembly itself can be directly tuned by phosphorylation, adding an additional layer to an already complex mode of regulation for IMPDH that occurs at different levels.…”
Section: Discussionmentioning
confidence: 99%